Is There an Association Between Oxytocin Levels in Plasma and Pregnant Women's Mental Health?. (May 2021) - Serati, Marta; Grassi, Silvia; Redaelli, Marta; Pergoli, Laura; Cantone, Laura; La Vecchia, Adriano; Barkin, Jennifer L.; Colombo, Elisa; Tiso, Giulia; Abbiati, Cristina; Bollati, Valentina; Buoli, Massimiliano
BACKGROUND: Mood and anxiety disorders are prevalent in women during peripartum.AIMS: Purpose of the present article was to study the relationship between oxytocin (OT) plasma levels and affective symptoms in women during the third trimester of pregnancy.METHODS: Thirty-four pregnant women (13 with an affective disorder, 9 with preeclampsia, and 12 controls) were evaluated through the Edinburgh Postnatal Depression Scale (EPDS), the State/Trait Anxiety Inventory Form Y (STAI-Y), and the Prenatal Attachment Inventory (PAI). A blood sample was collected from all participants, and OT plasma levels have been compared between diagnostic groups. The total sample has been divided into two groups, according to OT median plasma levels, and compared using (a) χ 2 tests for qualitative variables and (b) a multivariate analysis of covariance for quantitative ones.RESULTS: No statistically significant difference was found among the diagnostic groups in terms of OT plasma levels ( F = 0.49, p = .62). Women with lower OT plasma levels, independent from the presence of preeclampsia or an affective disorder, showed worse EPDS and STAI-S total scores than individuals with higher hormone levels ( F = 5.93, p = .02 and F = 7.57, p = .01, respectively).CONCLUSIONS: OT may play a role in the etiology of anxious/depressive symptoms during perinatal period independent from a medical or psychiatric diagnosis. This result has a clear effect on the quality of the relationship of patients with mental health professionals, including nurses, and higher levels of this hormone, in the light of its anxiolytic and antidepressive effect, may make easier medical and nursing procedures.